(untitled) (Studia Prawnicze / The Legal Studies, 1983)
The article analyses legal position of the Prime Minister in the light of all legal regulations, not only the Constitution of the Polish People’s Republic. Having characterized the regulations in general terms the author discusses in separate parts: 2) influence of the Prime Minister on the structure, composition and work of the Council of Ministers, 3) influence on the composition and activity of the Presidium of Government and other organs of the Council of Ministers, 4) influence on the organization and work of particular departments, 5) influence on central authorities and other government institutions, 6) direct influence of the Prime Minister on the Polish science, 7) management of local state administration, 8) Prime Minister as a chief organ of state administration, 9) legislative activities of the Prime Minister The work ends with Part 10 in which the author formulates conclusions and postulates de lege ferenda. The author criticizes many legal regulations and their application and suggests certain modifications in this field. First of all, he points to the fact that the posi tion of the Prime Minister resulting from the regulation considerably differs from that defined by the Constitution. The Prime Minister not only directs the work of the Council of Ministers and Presidium of Government but is also a monocratic state administration organ with very wide competences. He passes opinions on the provisions on tic appointment of the Council of Ministers, and its works, and on the position of vice-presidents of the Council of Ministers and other ministers — heads of departments, formulating various conclusions, i.a., on weakening a collegiate character of the Council of Ministers. He also evaluates the position of central government offices and other state institutions as well as local administration organs. The author formulates many conclusions, i.a., to relieve the Prime Minister of too many tasks fulfilled by him as a monocratic organ in order to make his function more real and strengthen it.